Peranan Keterampilan Berbahasa Inggris Pramusaji Dalam Meningkatkan Kualitas Pelayanan Di Compass Rose Restoran Hotel The Anmon Resort Bintan - Williandani, Mega (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2024)
This study examines the role of waiters' English language skills in improving service quality at Compass Rose Restaurant Hotel The ANMON Resort Bintan. As an international language, English plays a vital role in the hospitality industry, especially in the interaction between waiters and foreign guests. This study aims to analyze the level of waiters' English language skills, identify their impact on service quality, and formulate recommendations for service improvement. The method used in this study is a qualitative approach with data collection techniques through direct observation and in-depth interviews. The research informants consisted of 1 food and beverage manager, 1 supervisor, 10 waiters, and 6 restaurant guests, who were selected to provide comprehensive data on the role of English language skills in the context of restaurant service. The results of the study indicate that the waiters' English language skills are still not optimal, especially in the speaking aspect. This limitation has an impact on miscommunication in the food and beverage ordering process, which results in inconsistencies in orders and complaints from guests. This condition has a significant impact on the level of guest satisfaction and overall service quality. Based on these findings, this study recommends the importance of a consistent and structured English language training program under the coordination of the food and beverage manager. This program is aimed at improving the English language competence of waiters, especially in practical communication aspects relevant to service tasks in restaurants. The implementation of these recommendations is expected to improve the quality of service and create a more satisfying dining experience for Compass Rose Restaurant guests.